Politics and the Professors: The Great Society in PerspectiveAaronHenry J.. Politics and the Professors: The Great Society in Perspective (Washington, D.C.: The Brookings Institution, 1978) 185 pp., $9.95; paperback, $3.95. - Kolasa, Blair J. (Academy of Management Review, 1979)
This article presents a review of the book ?Politics and the Professors: The Great Society in Perspective,? by Henry J. Aaron.